Lógica Fuzzy aplicada à geologia - Wasques, Vinícius Francisco [UNESP] (2015)
This work presents some basic de nitions of fuzzy set theory and some theoretical examples that in most of the texts are left as an exercise for the reader. Thus, it is intended that the text is more didactic, complete and can be used to introductory courses theory . Some applications, focused on the Geology eld, are also presented. Highlight the proposed modeling performed using geophysical [1] and a system based on fuzzy rules for study sites in Rio Claro region (São Paulo - Brazil) that are more conducive to drill wells with good flow